Crystal structure of 2-chloro-11-(((fluoromethyl)sulfonyl)methyl)-6-methyl-6,11-dihydrodibenzo[c,f][1,2]thiazepine 5,5-dioxide, C16H13ClFNO4S2 - Fu Shaoyan; Liu Hongqian; Gao Yanrong; Wang Ji; Tang Wenqiang (Zeitschrift für Kristallographie - New Crystal Structures)
C16H13ClFNO4S2, monoclinic, P21/c (no. 14), a = 8.9984(2) Å, b = 18.0668(6) Å, c = 10.3178(3) Å, β = 95.5070(10)°, V = 1669.65(8) Å3, Z = 4, Rgt(F) = 0.0405 wRref(F2) = 0.1048, T = 150 K.